Geometrically frustrated magnetism in the pyrochlore Er2Ti2-xSnxO7 and in the disordered fluorites R2Zr2O7 (R = Dy, Ho, Tb) - Ramón, Jonathan Gustavo Acosta (2020)
In the geometrically frustrated magnets, competing magnetic interactions together with the lattice structure inhibit the system of establishing long-range order. The tetrahedral arrangement of the magnetic R ions in the pyrochlores R2M2O7 manifests the development of intriguing magnetic states which have been investigated vastly in the literature. However, the physical properties of the R ions in frustrated magnets are strongly affected when structural disorder is introduced. Recently, research probing disorder has provided interesting insights in XY pyrochlores, spin ices and spin liquids. In this work, we study the dilution of the nonmagnetic sublattice of M (Ti/Sn) in the pyrochlores Er2Ti2-xSnxO7 (x=0-2), and the defect-fluorites R2Zr2O7 (R = Dy, Ho and Tb) in which the R moments randomly reside on a sublattice together with the nonmagnetic Zr ions. The erbium compounds possess a strong local planar anisotropy, and with the dilution of the M sublattice, we study the evolution of the magnetic moment for all the x compositions starting from the 2 to the Palmer-Chalker configuration trough a specific-heat analysis. In-field experiments suppress the long-range order transition and the H-T phase diagram exhibits two different trends for small and high x values. Ac magnetic susceptibility and specific heat studies have been performed in the disordered-fluorites R2Zr2O7. Antiferromagnetic correlations and similar magnetic moment were found in Dy2Zr2O7 and Ho2Zr2O7, different from the ferromagnetic interactions in spin ices Dy2Ti2O7 and Ho2Ti2O7. Magnetic specific heat revealed a correlation broad peak around 2 K for the disordered fluorites as well as no Pauling\'s residual entropy was observed, contrary to the pyrochlore spin ices. Disorder in both fluorites preclude the development of spin-ice correlations and exhibit fluctuating spins; with a significant amount of susceptibility, which do not freeze into a canonical spin glass. Neutron scattering in Dy2Zr2O7 confirms no long-range order and antiferromagnetic correlations which remain dynamic down to 40 mK. These correlations extend over the length of 6.6 A and with an external field of 4 T expand to 23.6 A. Tb2Zr2O7 presents no long-range order and exhibits spin fluctuations down to 100 mK. Dynamic measurements display a frequency-dependent maximum and different models to its shift temperature reveal a canonical spin-glass transition around 2.2 K.